Pengaruh Pengangguran, Tingkat Tenaga Kerja Dan Kemiskinan Terhadap Ketimpangan Pendapatan Di Sumatra Utara - Syahputra, Andi; Daffa, Datuk Sazli; Siahaan, Fauzan Zuhri (Jurnal Manajemen Akuntansi (JUMSI), 2024)
North Sumatra is one of the provinces in Indonesia that faces challenges in reducing the income gap among its population. In this context, unemployment, labor levels, and poverty were identified as factors that might influence income inequality. This study aims to analyze the effect of unemployment, labor levels, and poverty on income inequality in North Sumatra. This research method uses a quantitative approach using secondary data collected from official sources such as BPS (Badan Pusat Statistik) and Related Literature. The data collected includes unemployment rates, labor rates, poverty rates, and income inequality rates in North Sumatra over a period of time. The results of the analysis showed that poverty has a significant relationship with income inequality in North Sumatra. High levels of poverty can lead to imbalances in the distribution of income, resulting in greater disparities between groups of people. In addition, the level of employment also has an influence on income inequality. Low labor rates can hinder economic growth and result in inequality in income distribution.